Strategi Peningkatan Daya Saing TV Kabel Lokal (Studi Kasus PT DKM) - Amru, M Kadafi; Daryanto, Heny K; Sanim, Bunasor (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2018)
PT DKM is a company engaged in the field of Cable TV located in Payakumbuh. By the end of 2016 there are 3,037 subscribers. Based on internal data of PT DKM, network coverage and cable TV subscribers has reached 40% of Payakumbuh's residential area. Position of PT DKM as a market leader in Pay TV industry in Payakumbuh has not shown that PT DKM as a strong company that can win the competition in the long run. Strategic planning of local cable TV PT DKM needs to be analyzed in order to win the competition in Pay TV industry in Payakumbuh. The purpose of this study is (1) analyze the condition of competition PT DKM in pay TV industry in Payakumbuh, (2) to analyze internal and external factors of PT DKM, and (3) to formulate alternative strategies that can be implemented to improve the competitiveness of PT DKM. This research uses Porter's Five Forces analysis method, EFE (External Factor Evaluation), IFE (Internal Factor Evaluation), IE (Internal External) and SWOT (Strength Weaknesses, Opportunities and Threats) matrix, and ANP (Analytical Network Process) to determine the best alternative strategy for increasing competitiveness of PT DKM. Result of the ANP analysis show that condition of pay TV industry competition in Payakumbuh is at a condusive level. Internal factors that have the highest score of strength are highly competitive subscription prices and the main drawback is the limited number of favorite channels. While the dominant external factors in the form of opportunities is the number of cable TV content providers; and corporate threats of increasing competitors. Based on analysis the most recommended strategy to improve the competitiveness of PT DKM is a strategy to increase cooperation with the best content provider.